Measuring Client Satisfaction and Engagement: The Role of a Mentor Parent Program in Family Drug Treatment Court. (February 2016) - Drabble, Laurie A.; Haun, Lisa L.; Kushins, Hilary; Cohen, Edward
Abstract: Parent engagement is an important intermediate outcome in Family Drug Treatment Court (FDTC) and child welfare services. This study explored the utility and reliability of a client satisfaction and engagement survey designed to measure interim outcomes of a Mentor Parent Program, operating in conjunction with a FDTC. Findings suggest the survey is a useful, parsimonious and reliable tool for measuring key dimensions of parent mentor services including client engagement; client‐centered support and empowerment; and help with systems navigation and accessing resources. The survey may be adapted for use in other FDTC or parent mentor contexts.